2012
DOI: 10.1007/s12262-012-0492-x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study Comparing Non-absorbable Polypropylene (Prolene®) and Delayed Absorbable Polyglactin 910 (Vicryl®) Suture Material in Mass Closure of Vertical Laparotomy Wounds

Abstract: Wound dehiscence is a postoperative complication encountered following abdominal surgery. A prospective randomized study was conducted to compare the incidence of wound dehiscence with a delayed absorbable and a nonabsorbable suture material in the mass closure of vertical laparotomy wounds. In one group, 100 patients were analyzed after closure with Prolene®, and in another group, 100 patients were analyzed after closure with Vicryl®. The incision was closed by continuous far and near suture technique using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In study by Pandey S et al, overall incidence of wound dehiscence was 11.5% and 17% in patients in whom mass closure was done with Vicryl. 8 In current study 12.6% of patients developed wound dehiscence which co-relates with many of Asian studies. Moreover, the higher incidence may be because the study included only emergency cases.…”
Section: Discussionsupporting
confidence: 75%
“…In study by Pandey S et al, overall incidence of wound dehiscence was 11.5% and 17% in patients in whom mass closure was done with Vicryl. 8 In current study 12.6% of patients developed wound dehiscence which co-relates with many of Asian studies. Moreover, the higher incidence may be because the study included only emergency cases.…”
Section: Discussionsupporting
confidence: 75%
“…), sound surgical wound closure remains the only potentially modifiable factor to prevent wound dehiscence .Many methods have been advocated to prevent AWD including the use of different type of suture material, different techniques of suturing including tension sutures, use of relaxing incisions and even use of absorbable mesh. (13)(14)(15)(16)(17)(18) The hypothesis of our study was partly based on the intraoperative findings at the time of revision of dehisced wounds. A common finding was sutures cutting through the fascia leading to loosening of the whole repair in cases of continuous wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one studies (summarised in Table 1) were identified that were appropriate in their question and SURGERY IN GENERAL Table 1 Author quality. These included studies investigating polyglactin, 1,4,[6][7][8][9][10][11][12][13][14] polydioxanone (PDS), 5,[15][16][17][18][19][20][21][22][23][24][25][26][27] polypropylene, 28,29 nylon, [30][31][32] polyglycolic acid (PGA), 33 polyglyconate, triclosan-coated polyglactin, triclosan-coated polydioxanone, Ethibond®, steel, poly(L-lactide-co-glycolide) (PLG) and Polysorb®.…”
Section: Introductionmentioning
confidence: 99%